Pengaruh Sumber Bahan Organik terhadap Kandungan Kimia Mikroorganisme Lokal (MOL) - Yovita Yasintha Bolly; Julianus Jeksen (Agriculture - Jurnal Ilmu Pertanian, 2024)
MOL can be used directly as a liquid fertilizer because it contains complete nutrients (macro and micro) for plant growth and production, although the nutrient content is relatively low. To determine the nutrient content of MOL, an analysis was conducted at the Soil Chemistry Laboratory, Faculty of Agriculture, Nusa Cendana University, Kupang. The purpose of this study was to determine the macronutrient content (N, P, K, and organic carbon), and the micronutrient content (Mn, Fe, Cu, Zn), as well as the pH and C/N ratio of the resulting local microorganisms. The study was conducted at the Nusa Cendana University experimental garden for approximately four months, from February to July 2024. The macronutrient content of MOL was 16.95% organic carbon, 2.06% nitrogen, 0.29% phosphorus, and 1.85% potassium. 8.91% C-Organic, 2.79% N, 0.34% P, 1.32% K, based on gamal leaves; 0.23% C-Organic, 1.23% N, 0.18% P, 0.80% K, based on lamtoro; 3.44% C-Organic, 1.53% N, 0.20% P, 1.29% K, based on mustard green waste; 1.11% C-Organic, 2.78% N, 0.33% P, 1.17% K, based on cow rumen and the content of micro nutrients MOL research results are 4.01% Mn, 108.78ppm Fe, 0.03ppm Cu, 1.73ppm Zn, pH 4.07 and C/N Ratio 8.23 based on kerinyuh; 3.12% Mn, 100.91 ppm Fe, 0.03ppm Cu, 1.71ppm Zn, pH 4.89 and C/N Ratio 3.20 based on gamal leaves; 3.01% Mn, 101.11ppm Fe, 0.03ppm Cu, 1.70ppm Zn, pH 5.10 and C/N Ratio 0.18 based on lamtoro; 3.38% Mn, 104.5ppm Fe, 0.02ppm Cu, 1.65ppm Zn, pH 4.89 and C/N Ratio 2.25 made from mustard green waste. 3.70% Mn, 106.82ppm Fe, 0.03ppm Cu, 1.69ppm Zn, pH 4.98 and C/N Ratio 0.40 made from cow rumen.